In-culture coronary stenting in an ex vivo vascular bioreactor - Razzi, F.; Bobi, J.; Stijnen, M.; van Esch, J. H.; Duncker, D. J.; van Steijn, V.; van Beusekom, H. M. M. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEx vivo vascular bioreactors that enable interventions in arteries from slaughterhouse surplus hearts present valuable alternatives to animal models to test cardiovascular stents. However, the knowledge for stent implantation during ex vivo culture in slaughterhouse coronary arteries is limited. The objective of the study is two-fold: first, to determine culture settings, the time point and optimal conditions for in-culture stent implantation using surplus right coronary arteries (RCAs) from swine with known in vivo RCA diameters; and second, to implement the gained insights to culture and stent RCAs obtained from slaughterhouse hearts (unknown in vivo diameter).MethodsSwine RCAs were mounted, cultured and stented in an ex vivo vascular bioreactor (VABIO) under conditions of flow and pressure. The bioreactor culture and stenting protocols were optimized using a step wise approach. In Step 1, the RCAs dissected from in-house swine hearts, with known diameters, were cultured until endothelialized as the ideal time point for stenting, and the stent implantation procedure was optimized. In Step 2, the successful ex vivo stent implantation procedure was repeated in slaughterhouse RCAs. Structural changes of the RCAs were assessed by ultrasound imaging during culture. The morphology of the RCAs at the end of culture was assessed by histology.ResultsThe RCAs adapted to the ex vivo environment, stabilizing their diameter in the range of the in vivo diameter after day 3, which was selected as the earliest time point for stenting. Because stent implantations caused mural dissections in the RCAs, visible with ultrasound imaging and confirmed by histology, we developed an external support for the RCA. This was found to be critical for better physiological intravascular pressures and to minimize dissections upon stent implantation. Finally, the stent implantation procedure was successfully replicated in slaughterhouse arteries.ConclusionsOur study demonstrates the feasibility of in-culture ex vivo stent implantation in the VABIO, providing important requirements and useful insights for in vivo mimicking stent implantation, for future investigations in slaughterhouse arteries.